Nearly a third of abnormalities found after first‐trimester screening are different than expected:10‐year experience from a single center. (27th January 2013) - Alamillo, Christina M. L.; Krantz, David; Evans, Mark; Fiddler, Morris; Pergament, Eugene
ABSTRACT: Objective: This study aimed to assess the efficacy of first‐trimester aneuploidy screening in a single clinical setting. Methods: Maternal age, nuchal translucency, and maternal serum levels of pregnancy‐associated plasma protein A and free beta human chorionic gonadotrophin comprised first‐trimester risk assessment for Down syndrome and trisomies 13/18. Means, screen positive rates, detection rates, and predictive values were calculated for Down syndrome and trisomies 13/18. Results: Of the 23 329 first‐trimester screenings, 6.3% were screen positive: 5.7% for Down syndrome only, 0.4% for trisomies 13/18 only, and 0.3% for Down syndrome and trisomies 13/18. An abnormal karyotype was present in 3.9% of screen positives for Down syndrome, 13.8% of screen positives for trisomies 13/18, and 45.9% of screen positives for both Down syndrome and trisomies 13/18. Of the 97 pregnancies found to have an abnormal karyotype, 29.9% had chromosome abnormalities other than trisomy 13, 18, or 21, with expected clinical outcomes ranging from likely benign to uniformly lethal. Conclusion: As expected, first‐trimester screening is effective for detecting aneuploidy for chromosomes 13, 18, and 21; however, a significant number of chromosomally abnormal pregnancies initially identified by first‐trimester screening have a different karyotype. With the possible exception of 47, XYY and 45, X, the dataset suggested that these different chromosome complements were likely to be randomly distributed. Nevertheless, prior to diagnostic testing, prospective parents should be counseled concerning the possibility of a chromosome abnormality other than the trisomies 13, 18, or 21. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? First trimester screening utilizes four variables: maternal age, nuchal translucency, and maternal serum PAPP‐A and free beta hCG. It is an effective means of detecting trisomies 13, 18, and 21. What does this study add? A significant number of chromosomally abnormal pregnancies identified by first trimester screening have a karyotype other than trisomy 13, 18, or 21. Prospective parents should be counseled concerning the possible presence of a different chromosome abnormality, including 45, X Turner syndrome.